PENGARUH KOMPENSASI, SEMANGAT KERJA DAN LINGKUNGAN KERJA TERHADAP KINERJA PEGAWAI DINAS PENDIDIKAN DAN KEBUDAYAN KABUPATEN INDRAGIRI HULU - Pamelia Deswita (Program Pascasarjana Universitas Wijaya Putra Surabaya, 2018)
This study aims to describe the influence of the compensation, spirit at work and work environment toward the performance of employees of Department of Education and Culture Indragiri Hulu District. This study also aims to know and examine the influence of both simultaneously and partially compensation, spirit at work and work environment toward the performance of employees in Department of Education and Culture Indragiri Hulu District. This research refers to survey research and the type of data analysis used as research including quantitative research. The research was conducted in the Department of Education and Culture Indragiri Hulu District with the population is amounting to 66 people. The sampling technique used in this study used a sampling census that is all members of the population into a sample of research. The result of data analysis shows that compensation, spirit at work and work environment have both simultaneously and partially a significant influence toward the performance of employees of Department of Education and Culture Indragiri Hulu District.